UPAYA MENINGKATKAN KEAKTIFAN SISWA KELAS V MELALUI PENERAPAN DISKUSI KELOMPOK DENGAN METODE PROJECT BASED LEARNING (PJBL) PADA MATA PELAJARAN IPAS - Prastyawan, Luky; Indawati, Ninik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve student engagement through the application of the Project-Based Learning (PjBL) model combined with group discussions in fifth-grade science lessons at SDN Tanjungrejo 2 Malang. The study employed the Kemmis and McTaggart Classroom Action Research (CAR) model, which consists of planning, action, observation, and reflection, conducted in two cycles. Twenty-seven students participated in the study. Data collection techniques included observation, questionnaires, documentation, and tests. The results showed that the implementation of the PjBL model significantly increased student engagement. The percentage of students categorized as active and very active increased from 48% in cycle I to 85% in cycle II, representing a 37% increase, exceeding the success indicator of 75%. This increase in engagement was evident in student involvement in discussions, their courage to express their opinions, and their group collaboration. Therefore, the PjBL model effectively increased student engagement in fifth-grade science lessons.